2019
DOI: 10.1038/s41598-019-47501-0
|View full text |Cite
|
Sign up to set email alerts
|

Role of procalcitonin as a predictor in difficult laparoscopic cholecystectomy for acute cholecystitis case: A retrospective study based on the TG18 criteria

Abstract: Difficult laparoscopic cholecystectomy (DLC) is difficult to precisely predict before operation. This observational cohort study aimed to evaluate the predictive value of procalcitonin (PCT) for DLC in patients with acute cholecystitis (AC). A total of 115 patients were included in the study from January 2017 to April 2018. Multiple logistic regression and receiver-operating characteristic (ROC) were performed to evaluate the predictive value of PCT levels in DLC. Patients with DLC had significantly higher Tok… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(28 citation statements)
references
References 18 publications
0
16
0
Order By: Relevance
“…In this study, some surgical videos were not available, and it was difficult to evaluate these cases. Therefore, we adopted operative time and blood loss, which were thought to be the indicators of DLC in other studies 7,8 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, some surgical videos were not available, and it was difficult to evaluate these cases. Therefore, we adopted operative time and blood loss, which were thought to be the indicators of DLC in other studies 7,8 …”
Section: Discussionmentioning
confidence: 99%
“…There have been several studies addressing the prediction of DLC before surgery. Some authors concluded that serum C‐reactive protein (CRP) level or procalcitonin level reflect local inflammation and are useful in predicting DLC 6,7 . Other studies predicted DLC by assessing local inflammation using CT imaging or abdominal ultrasound examination 8,9 .…”
Section: Introductionmentioning
confidence: 99%
“…24 Although Wu et al asserted that procalcitonin is an excellent predictor to understand the difficulty of laparoscopic cholecystectomy in patients diagnosed with acute cholecystitis, more evidence is needed on this issue. 25 In high-risk patients, mortality from laparoscopic cholecystectomy is mainly associated with overall mortality. 26 ASA scores of the patients were analyzed in our study in that respect.…”
Section: Complicationsmentioning
confidence: 99%
“…Patients undergoing laparoscopic cholecystectomy due to symptomatic cholelithiasis (with biliary colic) were included. Those patients with rheumatological diseases or concomitant acute infections 4 , preoperative diagnosis of gallbladder cancer 1 , Mirizzi syndrome 3 , acute cholecystitis 22 , choledocholithiasis 8 and acute pancreatitis6 were excluded from the study.…”
Section: Methodsmentioning
confidence: 99%